ANALYSIS OF ENGLISH JOB APPLICATION LETTER WRITING SKILLS AMONG ENGLISH EDUCATION STUDENTS - Habib Azizi NST; Muhammad Sobri; Rahmat Fais; Muhammad Hasyimsyah Batubara (Journal of Advances in Linguistics and English Teaching (JALET), 2026)
Writing competence is one of the most essential skills that English Education students must master to support both academic and professional communication. Among various forms of professional writing, job application letters play a significant role in helping graduates present their qualifications effectively to potential employers. This study aims to analyze the English job application letter writing skills of English Education students. The research employed a descriptive qualitative design involving 30 students from an English Education Study Program. Data were collected through documentation of students’ job application letters and analyzed based on letter structure, grammar, vocabulary, and language formality. The findings reveal that although most students were able to construct the general structure of a job application letter appropriately, many still experienced difficulties in grammatical accuracy, formal vocabulary selection, and the maintenance of professional tone. Several students used informal expressions and inappropriate sentence structures that reduced the effectiveness of their letters. Nevertheless, some participants demonstrated adequate ability in presenting information clearly and persuasively. The study concludes that students’ job application letter writing skills require further improvement, particularly in linguistic accuracy and professional correspondence conventions.